The 2024 resurgence of Bordetella pertussis in Brazil and a decade-long epidemiological overview - Sansone, Nathália Mariana Santos; Boschiero, Matheus Negri; Marson, Fernando Augusto Lima (Frontiers in Public Health, 2025)
Pertussis, or whooping cough, is a highly contagious respiratory illness caused by Bordetella pertussis. It primarily affects humans by adhering to the cilia of the upper respiratory tract, releasing toxins that impair ciliary function, and inducing inflammation. It is transmitted through respiratory droplets, and the disease is particularly severe in infants under 1 year of age, often resulting in high morbidity and frequent admission to intensive care units. Globally, the incidence of pertussis has been increasing, with notable increases observed in countries such as the United States, Brazil, and Mexico. In Brazil, the number of reported cases increased sharply in 2024 to 7,438—with a 34.4-fold increase compared to 2023 (N = 216)—with 30 associated deaths, the first since 2021. While most cases still affect children under 14 years of age, infections among individuals over 15 years of age have also increased, suggesting a demographic shift. The number of hospitalizations increased from 236 in 2023 to 739 in 2024 (a 3.1-fold increase). Geographically, the South region recorded the highest number of cases (N = 3,579), followed by the Southeast (N = 3,134). Incidence rates mirrored this pattern, with the South reporting 11.5 cases per 100,000 inhabitants and the Southeast, 3.54 per 100,000 inhabitants. Despite a slight improvement in vaccination coverage, it remains below the World Health Organization’s recommended threshold of 90%. Vaccination—particularly with the pentavalent and diphtheria, tetanus, and acellular pertussis (DTaP) vaccines—remains a critical tool for outbreak prevention; however, waning immunity underscores the need for booster doses across age groups. The coronavirus disease 2019 (COVID-19) pandemic likely reduced transmission temporarily due to mitigation measures and also led to missed routine vaccinations. To address this resurgence, Brazil must prioritize increasing vaccination coverage, especially among children, strengthening epidemiological surveillance, and improving healthcare provider training in immunization practices.